High‐Capacity, Dendrite‐Free, and Ultrahigh‐Rate Lithium‐Metal Anodes Based on Monodisperse N‐Doped Hollow Carbon Nanospheres. Issue 44 (8th October 2020) - Liu, Yuping; Zhen, Yanzhong; Li, Taoran; Bettels, Frederik; He, Tao; Peng, Manhua; Liang, Yucang; Ding, Fei; Zhang, Lin
Abstract: To unlock the great potential of lithium metal anodes for high‐performance batteries, a number of critical challenges must be addressed. The uncontrolled dendrite growth and volume changes during cycling (especially, at high rates) will lead to short lifespan, low Coulombic efficiency (CE), and security risks of the batteries. Here it is reported that Li metal anodes, employing the monodisperse, lithiophilic, robust, and large‐cavity N‐doped hollow carbon nanospheres (NHCNSs) as the host, show remarkable performances—high areal capacity (10 mAh cm −2 ), high CE (up to 99.25% over 500 cycles), complete suppression of dendrite growth, dense packing of Li anode, and an extremely smooth electrode surface during repeated Li plating/stripping. In symmetric cells, a highly stable voltage hysteresis over a long cycling life > 1200 h is achieved, and a low and stable voltage hysteresis can be realized even at an ultrahigh current density of 64 mA cm −2 . Furthermore, the NHCNSs‐based anodes, when paired with a LiFePO4 (LFP) cathode in full cells, give rise to highly improved rate capability (104 mAh g −1 at 10 C) and cycling stability (91.4% capacity retention for 200 cycles), enabling a promising candidate for the next‐generation high energy/power density batteries. Abstract : The lithiophilic nitrogen‐containing functional groups of the N‐doped hollow carbon nanospheres (NHCNSs) can reduce the local current density and regulate the nucleation process of metallic Li electrodeposition when used as Li metal host. Hence, the Li@NHCNSs anodes show high areal capacity, dendrite‐free surface, and stable plating/stripping even at an ultrahigh current density.